The usefulness of a free thinned deep inferior epigastric artery perforator flap and measurement of the vascular pedicle length: A thin flap with a long pedicle. Issue 5 (May 2022) - Akita, Shinsuke; Nakaguchi, Toshiya; Tokumoto, Hideki; Yamaji, Yoshihisa; Arai, Minami; Yasuda, Saori; Ogata, Hideyuki; Tezuka, Takafumi; Kubota, Yoshitaka; Mitsukawa, Nobuyuki
Summary: Background: The thinned deep inferior epigastric perforator (DIEP) flap branching from the main trunk to the superolateral direction may be useful because of its long vascular pedicle. DIEP flap is used as an axial-pattern adipose flap. The vascular pedicle length of the thinned DIEP flap was investigated using originally developed software. The clinical application of the thinned DIEP flap was verified in a case series. Methods: In 40 patients with enhanced computed tomography (CT) data, the vascular pedicle length of the longest thinned DIEP flap was simulated using the software. A free thinned DIEP flap was used in 10 clinical cases of facial or breast reconstruction. Results: In all simulated cases, the vascular pedicle of the DIEP branching to the superolateral direction was the longest, and the vascular pedicle could be lengthened up to 34.8% by dissecting the vessels on the fascia as a vascular pedicle. In all the clinical cases, the reconstruction of a complex form defect or reconstruction requiring a long vascular pedicle could be achieved in one stage without any perioperative complications. The intraclass correlation coefficient between simulated pedicle length and dissected pedicle length was 0.99. Conclusion: Thinned DIEP flaps with long vascular pedicles could be elevated safely. Multiple adipose or muscle flaps could be combined without complications. The length of the winding vascular pedicle could be measured using imaging data using the software first developed in the present study. This software would be useful in the planning of a thinned DIEP flap and other free flaps.